2018
DOI: 10.21474/ijar01/6418
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corticosteroid Utilization Pattern in Tertiary Care Hospital, Dehradun.

Abstract: Background: Corticosteroids are widely used as potent antiinflammatory and immunosuppressive drugs to treat a wide range of diseases. This study evaluates the rational use of corticosteroid amongst hospitalized patients. Objectives: To investigate the utilization and evaluation pattern of corticosteroids in various department of tertiary care hospital. Methodology: A prospective observational study was conducted on 90 patients receiving corticosteroids in the various departments of ShriMahantIndiresh Hospital,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Based on disease conditions, the various routes of administration were applied to the exposed steroids, and in some instances, only one route of administration was applied to the patients; hence this can be due to the difference in the inclusion criteria of the study. A similar study was conducted for evaluation of corticosteroid utilization patterns in a tertiary care hospital (Dabral and Devesh 2018). These all data suggested that among various dosage forms of steroids use, injection was most widely/frequently used, followed by topical and oral forms.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Based on disease conditions, the various routes of administration were applied to the exposed steroids, and in some instances, only one route of administration was applied to the patients; hence this can be due to the difference in the inclusion criteria of the study. A similar study was conducted for evaluation of corticosteroid utilization patterns in a tertiary care hospital (Dabral and Devesh 2018). These all data suggested that among various dosage forms of steroids use, injection was most widely/frequently used, followed by topical and oral forms.…”
Section: Discussionmentioning
confidence: 85%
“…This will increase the adverse effects and can lead to dependence on these medications (Ambika et al 2014, Saraswat et al 2011. Many researchers has been reported the use of corticosteroid was irrational due to as there were a number of interactions observed mostly prescribed in geriatric patient (Dabral and Devesh 2018, Mirshad et al 2017, Nerurkar et al 2016, Stern 1996. Prescriptions need to be audited periodically to enhance the therapeutic effectiveness, to minimize the adverse effects, to provide critical feedback to prescribers and to analyse the execution of medical treatment standards.…”
Section: Introductionmentioning
confidence: 99%